2015
DOI: 10.3906/kim-1501-71
|View full text |Cite
|
Sign up to set email alerts
|

Influence of acid and heavy metal cation exchange treatments on methane adsorption properties of mordenite

Abstract: Abstract:In this study, the adsorption of methane (CH 4) capacities onto natural mordenite obtained fromİzmir, Turkey, and its cationic forms (CuM, AgM, FeM, and HM samples) were investigated at the temperatures of 0 and 25• C up to 100 kPa. Natural and modified samples were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF),Fourier transform infrared (FT-IR), thermogravimetry (TG-DTG), differential thermal analysis (DTA), scanning electron microscopy (SEM) coupled with energy dispersion spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Before adsorbing ethylene, for the nylon spectra, the typical peaks of the amide group were seen at 1535 cm –1 (amide II, C–N stretch, and CO–N–H bend) and 1637 cm –1 (amide I, CO stretch), those of −NH bending were seen at 3062 cm –1 , and those of −NH stretching were seen at 3286 cm –1 . , The FTIR bands of mordenite exhibited that the intense broad peaks of the Si–O stretching vibration were observed at 1035 cm –1 , and the bands at 1647 cm –1 were attributed to the bending vibration of H–OH. Isolated OH stretching at 3628 cm –1 was assigned to the interaction between the water hydroxyl and cations (Al–OH stretching). , It is noted that the characteristic band for the amide group at 1535 and 1637 cm –1 as well as the −NH vibration band at 3062 and 3286 cm –2 in the FTIR band of nylon-6 was clearly seen in the NMC 30. Furthermore, compared to the mordenite spectra, the stretching vibration peak of Si–O in FTIR bands of the NMC 30 was broadened and shifted to a lower wavenumber from 1035 to 1029 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before adsorbing ethylene, for the nylon spectra, the typical peaks of the amide group were seen at 1535 cm –1 (amide II, C–N stretch, and CO–N–H bend) and 1637 cm –1 (amide I, CO stretch), those of −NH bending were seen at 3062 cm –1 , and those of −NH stretching were seen at 3286 cm –1 . , The FTIR bands of mordenite exhibited that the intense broad peaks of the Si–O stretching vibration were observed at 1035 cm –1 , and the bands at 1647 cm –1 were attributed to the bending vibration of H–OH. Isolated OH stretching at 3628 cm –1 was assigned to the interaction between the water hydroxyl and cations (Al–OH stretching). , It is noted that the characteristic band for the amide group at 1535 and 1637 cm –1 as well as the −NH vibration band at 3062 and 3286 cm –2 in the FTIR band of nylon-6 was clearly seen in the NMC 30. Furthermore, compared to the mordenite spectra, the stretching vibration peak of Si–O in FTIR bands of the NMC 30 was broadened and shifted to a lower wavenumber from 1035 to 1029 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Isolated OH stretching at 3628 cm −1 was assigned to the interaction between the water hydroxyl and cations (Al−OH stretching). 16,42 It is noted that the characteristic band for the amide group at 1535 and 1637 cm −1 as well as the −NH vibration band at 3062 and 3286 cm −2 in the FTIR band of nylon-6 was clearly seen in the NMC 30. Furthermore, compared to the mordenite spectra, the stretching vibration peak of Si−O in FTIR bands of the NMC 30 was broadened and shifted to a lower wavenumber from 1035 to 1029 cm −1 .…”
Section: Methodsmentioning
confidence: 98%
“…The relative amount of zeolite before and after acid activation can be determined by comparing the intensity of natural zeolite with acid-activated zeolite (1 M H-Zeolite and 6 M H-Zeolite ). XRD results also showed that the zeolite activation process using acid caused an increase in the relative amount of mordenite and clinoptilolite [11].…”
Section: Synthesis and Characterization Of Fruit Waste-based Ethanolmentioning
confidence: 91%
“…200 As far as the adsorption of CH4 is concerned, several studies show that other materials such as activated carbon, and metal-organic frameworks (MOFs) typically outperform zeolites. 13,190,191,201 However, some CH4 adsorption studies on natural, ion-exchanged, and acid-treated Turkish zeolite 197 and mordenite 198 revealed that their adsorption capacity depends strongly on the nature of the cation present. Furthermore, the observed capacity values decrease with increasing temperature.…”
Section: Separation or Containment Of Alternative Fuelsmentioning
confidence: 99%